Experimental investigation on the steam injection profile along horizontal wellbore - Xiaohu Dong; Huiqing Liu; Yong Zhai; Changjiu Wang; Zhangxin Chen; Dongqing Liu (Energy Reports, 2020)
Horizontal well based thermal recovery processes have been widely applied to recover the heavy oil resources all over the world. But, the flow behavior of hot fluids along a horizontal wellbore is still unclear. In this paper, a scaled cylindrical wellbore model is designed to experimentally simulate the steam injection process using horizontal well. Based on this model, a set of experiments are firstly performed to analyze the steam injection profile along horizontal wellbore. And the effects of different sensitive parameters on stream conformance are discussed. Results indicate that different steam injection operation can yield a different heating performance. During steam injection process, the wellbore segments closed to the steam outflow point can have a better heating performance. In comparison, a high steam injection rate is more beneficial on the uniform steam conformance along horizontal wellbore. The two-ends steam injection strategy can produce a more uniform steam injection profile than the single heel/toe end injection method. The addition of non-condensable gas (NCG) can also improve the steam conformance along horizontal wellbore. Moreover, from the experimental observation, it is also observed that the permeability heterogeneity along the horizontal wellbore is a significantly important parameter on the steam injection profile. The well completion method tremendously impacts the steam conformance along horizontal wellbore. For field operation, in order to obtain a more uniform steam conformance, it should be avoided to place the horizontal well in a high heterogeneous area, and slotted liner will be the preferred method for a horizontal well based thermal recovery process.
Keywords: 330; Heavy oil reservoir; Horizontal well; Steam conformance; Steam injection; Thermal recovery